Long-Term Effectiveness of Dupilumab in Patients with Atopic Dermatitis: Results up to 3 Years from the RELIEVE-AD Study - Alexa B. Kimball; Dimittri Delevry; Min Yang; Chien-Chia Chuang; Zhixiao Wang; Gaëlle Bégo-; Bruno Martins; Eric Wu; Brad Shumel; Jessie Wang; Debra Sierka; Jingdong Chao; et al. (Adis, Springer Healthcare, 2023)
Abstract Introduction Atopic dermatitis (AD) can require long-term therapy. Few real-world studies have evaluated long-term effectiveness from the patients' perspective. The aim of this study was to evaluate patient-reported outcomes (PROs) during long-term dupilumab treatment. Methods Adults with moderate-to-severe AD who initiated dupilumab through the US manufacturer patient support program and participated in RELIEVE-AD (a prospective patient survey study with a 12-month follow-up) were recontacted 30-36 months post-initiation regardless of current dupilumab use. The online questionnaire consisted of PROs, including the Atopic Dermatitis Control Tool (ADCT), use of concomitant AD therapies, satisfaction with current therapy, global change in itch relative to before dupilumab initiation, non-itch skin symptoms (skin pain/soreness, hot/burning feeling, and sensitivity to touch), flares, Dermatology Life Quality Index, sleep problems, and the AD-specific Work Productivity and Activity Impairment Questionnaire. Results Of 698 patients who initiated dupilumab (baseline) and were recontacted, 425 completed the 30-36-month survey. Significant reductions from baseline were reported in concomitant AD therapy use (P < 0.05); 54.4% reported not using other AD medications vs. 12.8% at baseline. At 30-36 months, all results (non-itch skin symptoms, flares, sleep problems, health-related quality of life work/activity impairment, disease control, and treatment satisfaction) were similar to or incrementally better than the 12-month timepoint, with significant improvements vs. baseline (P < 0.001). Global change in itch was reported as "very much better" by 75.3% of respondents. Adequate disease control (score < 7 on ADCT) was reported by 80.7% of respondents, and 86.8% were satisfied with the treatment. Conclusions In clinical practice settings, patient-reported benefits of dupilumab were maintained in survey respondents during long-term treatment up to 36 months while the use of concomitant AD therapies reduced.